Distribution and diversity of Verrucomicrobia methanotrophs in geothermal and acidic environments. (18th April 2014) - Sharp, Christine E.; Smirnova, Angela V.; Graham, Jaime M.; Stott, Matthew B.; Khadka, Roshan; Moore, Tim R.; Grasby, Stephen E.; Strack, Maria; Dunfield, Peter F.
Summary Recently, methanotrophic members of the phylum Verrucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16S rRNA gene amplicons. Putative methanotrophic Verrucomicrobia were found in samples covering a broad temperature range (22.5–81.6°C), but only in acidic conditions (pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16S rRNA gene sequence clusters of putative methanotrophic Verrucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6°C) grouped with known thermoacidiphilic 'Methylacidiphilum' isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1°C) and a representative mesophilic methanotroph from this group was isolated (strain LP2A). Genome sequencing verified that strain LP2A possessed particulate methane monooxygenase, but its 16S rRNA gene sequence identity to 'Methylacidiphilum infernorum' strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic Verrucomicrobia. Using pmoA‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP2A‐like pmoA sequences in the cooler surface layers and 'Methylacidiphilum'‐like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic Verrucomicrobia. However, both were detected only in acidic geothermal environments.